Robust Deadbeat Predictive Current Regulation for Permanent Magnet Synchronous Linear Motor Drivers With Parallel Parameter Disturbance and Load Observer - Wang, Lijun; Zhao, Jiwen; Yang, Xing; Zheng, Zhilei; Zhang, Xiaohu; Wang, Lei (IEEE transactions on power electronics, 2022)
This article proposed a robust deadbeat predictive current regulation (DPCR) algorithm for permanent magnet synchronous linear motors (PMSLMs) drive based on parallel parameter disturbance and load observer (PPDLOB). First, to increase the dynamic performance of current loop, a modified DPCR algorithm considering control delay is induced by using a discrete-time PMSLM model. Second, the PPDLOB consists of parameter disturbance observer (PDOB) and load disturbance observer (LDOB) is designed on the basis of a variable gain exponential sliding mode method. The PDOB is used to overcome parameter mismatch problem of the modified DPCR, whereas the LDOB is utilized to estimate the load thrust and the observation is fed forward to the current loop for compensating external disturbance. Finally, a series of comparative experiments are conducted and the results verify the feasibility and correctness of the proposed method.